Cardiac myxoma: a comprehensive review - Chigozie C. Okongwu; Olaejirinde O. Olaofe (Journal of Cardiothoracic Surgery)
Abstract Heart tumours are a diverse group of tumours that may present with symptoms or be discovered incidentally when a patient is being evaluated for a physical or seemingly unrelated ailment. Cardiac myxoma, although rare, is the second most common benign primary cardiac tumours after papillary fibroelastoma. It occurs in sporadic form and familial form, as seen in Carney complex disorder. Cardiac myxoma can affect all age groups, but the majority manifests in their third to sixth decade of life, with a mean age of 50 years at diagnosis. There is a slight preponderance in females in a ratio of 2:1. Conversely, they are incredibly uncommon in fetuses and newborns but commonly diagnosed in children around a mean age of 9–10 years. About 90% originate in the atrium as a solitary or pedunculated mass. Within the atrial chamber, 75% occur on the left atrium close to the fossa ovalis, while others occur in the right atrium, ventricles, and valves. Serious complications often arise even in the absence of symptoms, and such complications include intracardiac obstruction, systemic and pulmonary emboli, as well as constitutional symptoms that mimic connective tissue and inflammatory diseases. There is no pathognomonic clinical presentation. Complete surgical excision of the tumour, including the use of robotic surgery, is the key component of a successful course of treatment. To monitor for tumour recurrence, long-term follow-up is frequently carried out with interval echocardiography. This review will focus on providing information on the various forms of cardiac myxoma, aetiology, molecular genetics, clinical presentation, histopathologic findings, differential diagnosis, treatment, and complications.